Context–based learning–a case study in the Central Highlands, Vietnam - Tra, Do Huong; Thanh Phuong, Nguyen Thi; Hai, Phung Viet; Nie, H’ Na My (International Journal of Evaluation and Research in Education (IJERE), 2025)
The Central Highlands (Vietnam) harbors a diverse array of traditional musical instruments belonging to 13 ethnic minority groups. However, this invaluable cultural heritage faces the imminent threat of being forgotten and lost due to the lack of generational transmission among the youth. Consequently, the preservation and development of these instruments have become a critical priority for the education sector. This study implemented context-based learning (CBL) approach in teaching the topic of sound-natural science in 7th-grade, to encourage students to engage in addressing issues related to the preservation of traditional musical instruments within their local communities. Through observations and in-depth interviews with nine “E De” ethnic minority students, the study found that students exhibited a strong interest in learning to craft and play traditional instruments. They recognized the importance of this learning in contributing to cultural preservation and demonstrated the ability to apply scientific knowledge effectively in the crafting and utilizing of these instruments. These findings underscore the potential of CBL as a powerful educational model for teaching cultural heritage in other countries. This approach not only deepens students’ understanding of cultural values and social responsibility but also fosters mutual understanding and respect among different cultures on a global scale.